Tuning the fused aromatic rings to enhance photovoltaic performance in wide band-gap polymer solar cells. (8th November 2016) - Dang, Dongfeng; Chen, Jinxiang; Zhou, Pei; Duan, Linrui; Bao, Xichang; Yang, Renqiang; Chen, Junwu; Zhu, Weiguo
Abstract: Two novel wide band-gap polymers of PFT1 and PFT2 were designed as the alternative to P3HT in organic electronics, in which the fused aromatic rings were utilized and altered to tune their molecular co-planarity and photovoltaic performance in solar cells. As observed, although PFT1 exhibited strong inter-molecular interaction, slightly twisted molecular structure was observed, thus leading to an inferior PCE value of 1.95% in BHJ solar cells and holes mobility of 2.04 × 10 −2  cm 2  V −1  s −1 in OFETs in contrast to its isomeric polymer PBTFT. On the other hand, when the fused thiophene rings was tuned to construct PFT2, much planar polymer backbone was achieved, finally leading to the maximum PCE value of 3.34% in polymer solar cells and much enhanced holes mobility up to 3.93 × 10 −2  cm 2  V −1  s −1 in OFETs. Our results here further indicated that tuning the fused aromatic rings in polymer backbone could improve their charge transfer properties and enhance their photovoltaic performance in solar cells significantly. Graphical abstract: Highlights: Wide band-gap polymers were constructed utilizing fused aromatic rings in backbone. The co-planarity of polymer backbone was effectively tuned by changing the fused thiophene rings. The maximum PCE value of 3.34% was achieved in PFT2 based PSCs. Much enhanced holes mobility up to 3.93 × 10 −2  cm 2  V −1  s −1 was obtained in PFT2 based OFETs.